2003
DOI: 10.1046/j.1365-8711.2003.06309.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme galactic wind and Wolf--Rayet features in infrared mergers and infrared quasi-stellar objects

Abstract: We report, as a part of a long-term study of infrared (IR) mergers and IR quasi-stellar objects (QSOs), detailed spectroscopic evidence for outflow (OF) and Wolf-Rayet (WR) features in the nearby mergers NGC 4038/39 and IRAS 23128−5919 (with low-velocity OF); and the nearby QSOs IRAS 01003−2238 and 13218+0552 (with extreme velocity OF, EVOF). We also study the presence of EVOF in a complete sample of ultraluminous IR galaxies and QSOs ('The IRAS 1-Jy Survey', 118 objects). We found EVOF in IRAS 11119+3257, 143… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
155
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(175 citation statements)
references
References 111 publications
19
155
0
1
Order By: Relevance
“…They both show a spectrum dominated by molecular H 2 and weak Brγ emission. Our composite JHK spectroscopy reveals a poor emis- Lipari et al (2003). The continuum emission is steep and featureless of a powerlaw type.…”
Section: Notes On Individual Objectsmentioning
confidence: 77%
“…They both show a spectrum dominated by molecular H 2 and weak Brγ emission. Our composite JHK spectroscopy reveals a poor emis- Lipari et al (2003). The continuum emission is steep and featureless of a powerlaw type.…”
Section: Notes On Individual Objectsmentioning
confidence: 77%
“…Indeed, outflows have been observed in all gas phases in merging galaxies: ionized (e.g. [OIII]; Wilman et al 1999;Lipari et al 2003;Holt et al 2003;Holt et al 2006; Cicone et al 2012;Veilleux et al 2013;Cicone et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively they may be a young phase in quasar evolution. The latter together with the high occurrence of BALQSO in IRAS selected samples suggests that they may be a transition stage between ULIGs and QSOs (Voit et al, 1993;Lípari, 1994;Egami et al, 1996;Canalizo and Stockton, 2001;Lípari et al, 2003). In this scenario very young QSOs are ejecting their gaseous envelopes at very high velocity close to the initiation of the active phase of the black hole (Hazard et al, 1984).…”
Section: Evolution Of Uligsmentioning
confidence: 97%
“…Recently, Lípari et al (2003) identified possible Wolf-Rayet features in the spectra of some PG quasars. The identifying Wolf-Rayet signatures are in the visible and thus are only representative of the unobscured components.…”
Section: Wolf-rayet Starburstsmentioning
confidence: 99%
See 1 more Smart Citation